Implanting strategic management - Ansoff, H. Igor; Kipley, Daniel; Lewis, A.O; Helm-Stevens, Roxanne; Ansoff, Rick (Springer International Publishing Imprint: Palgrave Macmillan, 2019)
Coming more than 25 years after the last edition, this edition of the groundbreaking Ansoff work on the concepts and practical implementation of strategic management provides up-to-date case studies and simplified figures and offers a comprehensive approach to guiding firms through turbulent environments. In this age of digital transformation, the ability to respond quickly and strategically to unpredictable change can determine the success or failure of the firm. As an organization becomes more successful at implementing change, the ability to respond to changes in the environment will be entrenched in its culture. This book is based on a strategic success model which demonstrates how to optimize a firm's performance. For managers, students, and researchers wanting a step-by-step methodology on how to analyze a firm, this book will serve as an invaluable resource for thinking and acting strategically.